Profiles of endogenous circulating cortisol and bone mineral density in healthy elderly men. - Dennison, E; Hindmarsh, P; Fall, C; Kellingray, S; Barker, D; Phillips, D; Cooper, C (1999)
Exogenous glucocorticoids are known to increase the risk of osteoporosis. However, the contribution made by endogenous circulating cortisol concentrations to adult skeletal status remains unknown. We examined this issue in a sample of 34 healthy men, aged 61-72 yr. Venous blood samples were obtained under standard conditions every 20 min over a 24-h period. Measurements were made of serum cortisol and cortisol-binding globulin. Bone mineral density was measured at the lumbar spine and proximal femur using dual energy x-ray absorptiometry. Measurements were made at baseline and 4 yr later. There was a weak negative association between integrated cortisol concentration and lumbar spine bone density (r = -0.37; P < 0.05); similar relationships (P < 0.05) existed at three of five proximal femoral sites. There were also statistically significant positive associations between the trough cortisol concentration and bone loss rate at the lumbar spine (r = 0.38; P < 0.05), femoral neck (r = 0.47; P < 0.001), and the trochanteric region (r = 0.41; P = 0.02) over the 4-yr follow-up period. The cross-sectional relationships between cortisol concentration and bone density were removed by adjustment for body mass index, but the influence on bone loss rate remained significant after adjusting for adiposity, cigarette smoking, alcohol consumption, dietary calcium intake, physical activity, and serum testosterone and estradiol levels. These observations suggest that the endogenous cortisol profile of healthy elderly men is a determinant of their bone mineral density and their rate of involutional bone loss.